The psychological burden of retirement from sport - Esopenko, C.; Coury, J.; Pieroth, E. M.; Noble, J. M.; Trofa, D. P.; Bottiglieri, T. S. (Current Sports Medicine Reports, 2020)
Participation in sport is associated with numerous physical and psychological health benefits, but also can have negative consequences, such as career ending injuries, which may have long-term effects on mental health. Recent research suggests that involuntary retirement, due to injury, illness, or being cut from a sport, can be particularly detrimental. As such, this review focuses on the impact athletic retirement has on the psychological well-being of collegiate athletes. We provide an algorithm to inform clinical decision making regarding involuntary retirement, as well as recommendations for the development of support programs and educational resources for athletes struggling with career transition. Our aim is that in developing retirement algorithms, support programs, and educational resources for athletes who are retired from sport, we can intervene early thus reducing the potential long-term psychological burden they may experience.